2015
DOI: 10.1021/acs.jafc.5b00769
|View full text |Cite
|
Sign up to set email alerts
|

Study of Water Dynamics in the Soaking, Steaming, and Solid-State Fermentation of Glutinous Rice by LF-NMR: A Novel Monitoring Approach

Abstract: Solid-state fermentation (SSF) of starchy grain is a traditional technique for food and alcoholic beverage production in East Asia. In the present study, low-field nuclear magnetic resonance (LF-NMR) was introduced for the elucidation of water dynamics and microstructure alternations during the soaking, steaming, and SSF of glutinous rice as a rapid real-time monitoring method. Three different proton fractions with different mobilities were identified based on the degree of interaction between biopolymers and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(50 citation statements)
references
References 38 publications
(88 reference statements)
1
49
0
Order By: Relevance
“…However, the interaction of water vapor with peptides is extensive and strong, and the dynamics of the molecular sorption process are expected to be complex. Ordinarily, the multi‐exponential inversion of NMR relaxation behavior of foodstuff matrices is assigned to different moisture fractions existing within the multiphase biopolymer micro‐framework (Li and others ). Previous studies have shown that protons in peptide systems can be differentiated into several distinct populations through their NMR relaxation behavior, which provides unique insights into the microstructure of the peptide samples.…”
Section: Resultsmentioning
confidence: 99%
“…However, the interaction of water vapor with peptides is extensive and strong, and the dynamics of the molecular sorption process are expected to be complex. Ordinarily, the multi‐exponential inversion of NMR relaxation behavior of foodstuff matrices is assigned to different moisture fractions existing within the multiphase biopolymer micro‐framework (Li and others ). Previous studies have shown that protons in peptide systems can be differentiated into several distinct populations through their NMR relaxation behavior, which provides unique insights into the microstructure of the peptide samples.…”
Section: Resultsmentioning
confidence: 99%
“…Distributed multiexponential fitting of CPMG decay curves was performed in MultiExp Inv analysis software (Niumag Electric Corporation, Shanghai, China). An exponential distribution in CPMG testing is defined by using the following equation: Atrue(ttrue)=j=1nA2j exptrue(tT2jtrue)+ etrue(ttrue) where A ( t ) is the residual magnetization as a function of acquisition time t , n is the number of exponential functions or components in the sample, A 2 j and T 2 j are the spin–spin relaxation amplitude and time, respectively, of the component, and e is the residual error (Li et al, ). The relaxation data were analyzed using the SRIT regularization algorithm to obtain the corresponding T 2 relaxation spectra from the decay curve.…”
Section: Methodsmentioning
confidence: 99%
“…Multi-way chemometric analysis based on LF-NMR measurements was used to investigate the relationship of LF-NMR parameters and quality characteristics; PCA were highly considered in aquatic products among those methods [29][30][31]. Figure 4 demonstrated the component plot of the first two principal component PC1 and PC2 scores of HTS fillets during storage.…”
Section: Analysis Of Pcamentioning
confidence: 99%